2020
DOI: 10.1016/j.eucr.2019.101057
|View full text |Cite
|
Sign up to set email alerts
|

A case report of solitary neurofibroma of the Vas deferens

Abstract: Solitary neurofibroma of the male genital tract is a rare benign peripheral nerve sheath tumor which is considered to originate from the Schwann cell. Neurofibroma of the male genital tract has been reported extremely rarely in the literature. We present a case of neurofibroma of the Vas deferens in a 59-year-old patient. The clinical and pathological data of a patient with Neurofibroma of the Vas deferens were retrospectively analyzed and radical resection of the left side spermatic cord tumor was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Because pancreatic neurofibroma is very rare and there is a lack of large-scale research to statistically analyze its imaging characteristics and because the growth pattern of this tumor is very similar to that of malignant tumors, there is indeed a great possibility of misdiagnosis in clinical practice. Histopathology showed that the tumor was mainly composed of spindle cells, and the immunohistochemical results showed that the tumor expressed S-100 protein and CD34 protein, which was consistent with other reports ( 6 , 18 ).…”
Section: Discussionsupporting
confidence: 91%
“…Because pancreatic neurofibroma is very rare and there is a lack of large-scale research to statistically analyze its imaging characteristics and because the growth pattern of this tumor is very similar to that of malignant tumors, there is indeed a great possibility of misdiagnosis in clinical practice. Histopathology showed that the tumor was mainly composed of spindle cells, and the immunohistochemical results showed that the tumor expressed S-100 protein and CD34 protein, which was consistent with other reports ( 6 , 18 ).…”
Section: Discussionsupporting
confidence: 91%